A Drosophila ortholog of the human cylindromatosis tumor suppressor gene regulates triglyceride content and antibacterial defense. - Tsichritzis, T; Gaentzsch, P; Kosmidis, S; Brown, A; Skoulakis, E; Ligoxygakis, P; Mosialos, G (2007)
The cylindromatosis (CYLD) gene is mutated in human tumors of skin appendages. It encodes a deubiquitylating enzyme (CYLD) that is a negative regulator of the NF-kappaB and JNK signaling pathways, in vitro. However, the tissue-specific function and regulation of CYLD in vivo are poorly understood. We established a genetically tractable animal model to initiate a systematic investigation of these issues by characterizing an ortholog of CYLD in Drosophila. Drosophila CYLD is broadly expressed during development and, in adult animals, is localized in the fat body, ovaries, testes, digestive tract and specific areas of the nervous system. We demonstrate that the protein product of Drosophila CYLD (CYLD), like its mammalian counterpart, is a deubiquitylating enzyme. Impairment of CYLD expression is associated with altered fat body morphology in adult flies, increased triglyceride levels and increased survival under starvation conditions. Furthermore, flies with compromised CYLD expression exhibited reduced resistance to bacterial infections. All mutant phenotypes described were reversible upon conditional expression of CYLD transgenes. Our results implicate CYLD in a broad range of functions associated with fat homeostasis and host defence in Drosophila.